HFE H63D Polymorphism and the Risk for Systemic Hypertension, Myocardial Remodeling, and Adverse Cardiovascular Events in the ARIC Study. Issue 1 (January 2019) - Selvaraj, Senthil; Seidelmann, Sara; Silvestre, Odilson M.; Claggett, Brian; Ndumele, Chiadi E.; Cheng, Susan; Yu, Bing; Fernandes-Silva, Miguel M.; Grove, Megan L.; Boerwinkle, Eric; Shah, Amil M.; Solomon, Scott D.
Abstract : H63D has been identified as a novel locus associated with the development of hypertension. The quantitative risks for hypertension, cardiac remodeling, and adverse events are not well studied. We analyzed white participants from the ARIC study (Atherosclerosis Risk in Communities) with H63D genotyping (N=10 902). We related genotype status to prevalence of hypertension at each of 5 study visits and risk for adverse cardiovascular events. Among visit 5 participants (N=4507), we related genotype status to echocardiographic features. Frequencies of wild type (WT)/WT, H63D/WT, and H63D/H63D were 73%, 24.6%, and 2.4%. The average age at baseline was 54.9±5.7 years and 47% were men. Participants carrying the H63D variant had higher systolic blood pressure ( P =0.004), diastolic blood pressure (0.012), and more frequently had hypertension ( P <0.001). Compared with WT/WT, H63D/WT and H63D/H63D participants had a 2% to 4% and 4% to 7% absolute increase in hypertension risk at each visit, respectively. The population attributable risk of H63D for hypertension among individuals aged 45 to 64 was 3.2% (95% CI, 1.3–5.1%) and 1.3% (95% CI, 0.0–2.4%) among individuals >65 years. After 25 years of follow-up, there was no relationship between genotype status and any outcome ( P >0.05). H63D/WT and H63D/H63D genotypes were associated with small differences in cardiac remodeling. In conclusion, the HFE H63D variant confers an increased risk for hypertension per allele and, given its frequency, accounts for a significant number of cases of hypertension. However, there was no increased risk for adverse cardiovascular events or substantial left ventricular remodeling. Abstract : Supplemental Digital Content is available in the text.